Whose story is it anyway?: Collective memory, postmemory, and the use of the subjunctive mood in Katja Petrowskaja’s Vielleicht Esther, Nora Krug’s Heimat, and Heather Morris’s The Tattooist of Auschwitz - Hawks, Sophie Ivalee (My University, 2025)
The Holocaust has a complicated and multifaceted history, involving many diverse experiences. It is challenging to convey the true magnitude of the Holocaust properly. The collective memory, which integrates various tropes associated with and often synonymous with the Holocaust, informs the way that this event is remembered and described. This collective memory can be narrow and diminish the multitude of stories and experiences felt by the victims and survivors. Despite these shortcomings, Holocaust media often draws on this collective memory in order to engage a wide audience and guide their understanding of the event. Members of the second and third generations with postmemory of the Holocaust may utilize this collective memory as a mediator for their own exploration of their family histories. Authors writing from the standpoint of postmemory also employ the subjunctive mood as a tool to investigate the multitude of possibilities that may exist within their family history. In this report, I will analyze the role of the collective memory and the subjunctive mood in the novels Vielleicht Esther by Katja Petrowskaja and Heimat by Nora Krug, in contrast to the popular novel The Tattooist of Auschwitz by Heather Morris. This paper considers the various narrative strategies used to explore the legacy of the Holocaust and the impact that the strategies have on how we interpret and understand the Holocaust in the present day.
Keywords: Postmemory; Holocaust; Subjunctive; Collective memory; Vielleicht Esther; Heimat: Ein deutsches Familienalbum; The Tattooist of Auschwitz